Determinants of financial performance of insurance companies: Empirical evidence using Kenyan data - Kamanda Morara; Athenia Bongani Sibindi (Journal of Risk and Financial Management, 2021)
The drivers of financial success of the insurance industry are of interest to several players in any economy including the government; policymakers; policyholders; and investors. In Kenya; there have been relatively few studies on this topic; most of which look at narrow elements that determine insurance companies' performance. This article sought to explore the components contributing to the financial performance of insurance firms. We employed a sample consisting of 37 general insurers and 16 life insurers for the period running from 2009 to 2018 and utilised panel data methods in order to establish the determinants of financial performance of Kenyan insurers. The pooled OLS; fixed effects and random effects models were estimated with the financial performance measures (proxied by either ROA or ROE) as the dependent variables. The results of the study documented that insurer financial performance and size were positively related. The study also found that insurer financial performance was negatively related to the age variable. The study also unraveled that higher leveraged insurance companies performed better than their lowly geared peers. This article provides broad analyses of the various drivers of financial performance of the insurance industry in Kenya. The findings of this study contribute to the academic literature on the financial performance of the insurance sector in Kenya and Africa as a whole. Furthermore; it gives pointers to the management of insurance companies on the aspects of their business that would need greater attention to drive and sustain superior financial performance.
Keywords: G22; G32; 330; insurance; financial performance; solvency; Kenya